Minding the gap: towards a shared clinical reasoning lexicon across the pre-clerkship/clerkship transition - Robin K. Ovitsh; Shanu Gupta; Anita Kusnoor; Jennifer M. Jackson; Danielle Roussel; Christopher J. Mooney; Roshini Pinto-Powell; Joel L. Appel; Rahul Mhaskar; Jonathan Gold (Medical Education Online)
Teaching and learning of clinical reasoning are core principles of medical education. However, little guidance exists for faculty leaders to navigate curricular transitions between pre-clerkship and clerkship curricular phases. This study compares how educational leaders in these two phases understand clinical reasoning instruction. Previously reported cross-sectional surveys of pre-clerkship clinical skills course directors, and clerkship leaders were compared. Comparisons focused on perceived importance of a number of core clinical reasoning concepts, barriers to clinical reasoning instruction, level of familiarity across the undergraduate medical curriculum, and inclusion of clinical reasoning instruction in each area of the curriculum. Analyses were performed using the Mann Whitney U test. Both sets of leaders rated lack of curricular time as the largest barrier to teaching clinical reasoning. Clerkship leaders also noted a lack of faculty with skills to teach clinical reasoning concepts as a significant barrier (p < 0.02), while pre-clerkship leaders were more likely to perceive that these concepts were too advanced for their students (p < 0.001). Pre-clerkship leaders reported a higher level of familiarity with the clerkship curriculum than clerkship leaders reported of the pre-clerkship curriculum (p < 0.001). As faculty transition students from the pre-clerkship to the clerkship phase, a shared understanding of what is taught and when, accompanied by successful faculty development, may aid the development of longitudinal, milestone-based clinical reasoning instruction.